Relationship between Symptoms Resulting from Taking the Covid-19 Vaccine, Health and Knowledge - Salwa Muftah Eljamay; Mohammed Marri Younus; Emad Saleh Mousa Elgebaily; Hamza Khalifa (East Asian Journal of Multidisciplinary Research, 2022)
To prove the Effect of the Covid-19 vaccine and the symptoms resulting from the immune response. Questionnaires and personal interviews were taken from those vaccinated. 147 males (47.9%), 160 females (52.1%), mean and SD. Sequentially (1.48) (0.500), mean ages (10-90) years and SD sequentially (3.17) (1.413), mean and SD of sequential learning (2.96) (1.622), who received one dose was 99 (32.3%), and those who took two doses were 208 (67.8%). For those who have symptoms after vaccination, yes 141 (46.0%), no 42 (13.7%), and 124 (49.4) were unknown. And the relationship between symptoms after vaccination for gender R is (0.110), P-value = 0.054 = 0.05 which indicates a tiny relationship with symptoms after vaccination, were for age R (0.007), P-value (0.908) > 0.05, indicating no relationship between age and symptoms after vaccination, the relationship between chronic disease and appearance of symptoms, R= (0.724**), P –Value (0.000 < 0.005).